Hibernation-associated gene regulation of plasma proteins with a collagen-like domain in mammalian hibernators. - Takamatsu, N (1993)
In mammals, hibernation is expressed by only a limited number of species, and the molecular mechanisms underlying hibernation are not well understood. Recently, we have found plasma proteins which disappear from blood specifically during hibernation in a mammalian hibernator, the chipmunk. Here, we report the cDNA cloning of these chipmunk hibernation-related proteins, HP-20, -25, and -27, and analyses of their expression. All three proteins contain a collagen-like domain near the N terminus and are highly homologous to each other. Their mRNAs were detected only in liver in nonhibernating chipmunks, and in hibernating chipmunks, the amounts were reduced to less than 1/10 of those in nonhibernating chipmunks, indicating that HP-20, -25, and -27 mRNA expression is regulated similarly in association with hibernation. Southern blot analyses of the squirrel family with each of chipmunk HP-20, -25, and -27 cDNA revealed that a nonhibernating species (tree squirrel) as well as another hibernating species (ground squirrel) retained the corresponding genes. However, their transcripts were detected only with the hibernating species, and in hibernating ground squirrels, their levels were greatly reduced compared with those in nonhibernating animals, as were the cases with the chipmunk. These observations are the first line of evidence for occurrence of hibernation-associated gene regulation. The results would indicate the commitment of HP-20, -25, and -27 to hibernation and support the idea that genetic controls are involved in mammalian hibernation.